Association of rare, recurrent nonsynonymous variants in the germline of prostate cancer patients of African ancestry. Issue 5 (25th December 2022) - Wei, Jun; Beebe‐Dimmer, Jennifer; Shi, Zhuqing; Sample, Christopher; Yan, Guifang; Rifkin, Andrew S.; Sadeghpour, Azita; Gielzak, Marta; Choi, Sodam; Moon, David; Zheng, S. Lilly; Helfand, Brian T.; et al.
Abstract: Background: Although men of African ancestry (AA) have the highest mortality rate from prostate cancer (PCa), relatively little is known about the germline variants that are associated with PCa risk in AA men. The goal of this study is to systematically evaluate rare, recurrent nonsynonymous variants across the exome for their association with PCa in AA men. Methods: Whole exome sequencing (WES) of germline DNA in two AA PCa patient cohorts of Johns Hopkins Hospital ( N = 960) and Wayne State University ( N = 747) was performed. All nonsynonymous variants present in both case cohorts, with a carrier rate between 0.5% and 1%, were identified. Their carrier rates were compared with rates from 8128 African/African American (AFR) control subjects from The Genome Aggregation Database (gnomAD) using Fisher's exact test. Significant variants, defined as false discovery rate (FDR) adjusted p ‐value ≤ 0.05, were further evaluated in AA PCa cases ( N = 132) and controls ( N = 1184) from the UK Biobank (UKB). Results: Two variants reached a pre‐specified statistical significance level. The first was p.R14Q in GPRC5C (found in 0.47% of PCa cases and 0.01% of population controls); odds ratio (OR) for PCa was 37.46 (95% confidence interval CI 4.68–299.72), pexact = 7.01E‐06, FDR‐adjusted p ‐value = 0.05. The second was p.R511Q in IGF1R (found in 0.53% of PCa cases and 0.01% of population controls); OR for PCa was 21.54 (95%CI 4.65–99.76), pexact = 5.51E‐06, FDR‐adjusted p ‐value = 0.05. The mean percentage of African ancestry was similar between variant carriers and noncarriers of each variant, p > 0.05. In the UKB AA men, GPRC5C R14Q was 0.76% and 0.08% in cases and controls, respectively, OR for PCa was 9.00 (95%CI 0.56–145.23), pexact = 0.19. However, IGF1R R511Q was not found in cases or controls. Conclusions: This WES study identified two rare, recurrent nonsynonymous PCa risk‐associated variants in AA. Confirmation in additional large populations of AA PCa cases and controls is required.